Effect of interleukin-6 inhibition on coronary microvascular and endothelial function in myocardial infarction. Issue 19 (21st April 2017) - Holte, Espen; Kleveland, Ola; Ueland, Thor; Kunszt, Gabor; Bratlie, Marte; Broch, Kaspar; Michelsen, Annika E; Bendz, Bjørn; Amundsen, Brage H; Aakhus, Svend; Damås, Jan Kristian; Gullestad, Lars; et al.
Abstract : Objective: Interleukin-6 (IL-6) is a driver of inflammation and associated endothelial cell activation in acute coronary syndromes. We evaluated the effect of the IL-6 receptor antagonist tocilizumab on coronary microvascular function and endothelial dysfunction measured by coronary flow reserve (CFR) and markers of endothelial cell activation in patients with non-ST-elevation myocardial infarction (NSTEMI). Methods: This substudy was part of a two-centre, double-blind, randomised, placebo-controlled trial evaluating the effect of a single dose of tocilizumab in NSTEMI. Markers of endothelial cell activation (vascular cell adhesion molecule (VCAM)-1, intercellular adhesion molecule-1 and von Willebrand factor) were assessed in 117 patients. In 42 of these patients, 20 assigned to placebo and 22 to tocilizumab, we measured CFR. Blood samples were obtained at seven consecutive time points between day 1 and 3. CFR was measured by transthoracic echocardiography during hospitalisation and after 6 months. Results: Tocilizumab did not affect CFR during hospitalisation (tocilizumab: 3.4±0.8 vs placebo: 3.3±1.2, p=0.80). CFR improved significantly in both groups at 6 months. Patients in the tocilizumab group had significantly higher area under the curve for VCAM-1 (median 622 vs 609 ng/mL/hour, tocilizumab and placebo respectively, p=0.003). There were inverse correlations between VCAM-1 and CFR in the placebo (hospitalisation: r=−0.74, p<0.01, 6 months: r=−0.59, p<0.01), but not in the tocilizumab group (hospitalisation: r=0.20, p=0.37, 6 months r=−0.28, p=0.20). Conclusions: Tocilizumab did not affect CFR during hospitalisation or after 6 months. Tocilizumab increased VCAM-1 levels during hospitalisation, but this was not associated with reduced CFR in these patients.